Simulasi Numerik Distribusi Medan Magnet Aksial dan Radial pada Solenoida Berhingga Berbasis MATLAB - Muddasir, Fadhil; Khotimah, Siti Nurul (Green Publisher Indonesia, 2025)
This study aims to numerically analyze the distribution of axial and radial magnetic fields in a finite solenoid using MATLAB software. The simulation is based on classical magnetic field theory, particularly the Biot–Savart law, along with Pathak's analytical approach for modeling the radial field component. The primary focus is to understand the magnetic field behavior around a solenoid of finite length, which is commonly used in various electromagnetic applications. The simulation results reveal that the axial magnetic field remains relatively uniform within the central region of the solenoid but decreases significantly near its ends due to the fringe field effect. Meanwhile, the radial magnetic field outside the solenoid exhibits an exponential decay with increasing radial distance from the axis, consistent with the behavior of a magnetic dipole field. These findings offer preliminary validation of the theoretical models applied in the simulation while emphasizing the need for further experimental verification. This research is expected to contribute to the design, development, and optimization of experimental devices involving finite solenoids, particularly in applied physics and electromagnetic engineering contexts.